A Low-Cost Electroencephalography (EEG) Instrumentation for Epileptic Seizure Detection. (March 2020) - Bera, Tushar Kanti; Choudhary, Sunil; Maiti, Toushik; Prasad Barnwal, Suraj
Abstract: Noninvasive detection of epileptic seizures can help the patients to save themselves from sudden fall and assist the doctors to study the disease and treat the patient. Generally, an EEG based epileptic seizure detection system consists of EEG sensors, electronic instrumentation and a signal processing algorithm. In this paper, an EEG acquisition system (EAS) has been developed with a multi-stage amplifier and filter blocks. The instrumentation is studied, tested and evaluated with periodic signals generated with a function generator as well as the EEG-like signals simulated by virtual instrumentation (VI) developed with NI MyDAQ controlled by a Lab VIEW. The noise response of the instrumentation developed has been studied with SNR analysis. Results, obtained from the circuit simulation and experimentation conducted with EEG-like waveforms, show that the developed EAS is suitable to process the EEG signals and suitable for epileptic seizures detection systems.